PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI, DAN STRES KERJA TERHADAP MINAT KARYAWAN UNTUK MENINGGALKAN TEMPAT KERJA - Firmansyah, Bima Wadafi; Rohman , Fatchur (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This research aims to analyze job satisfaction, organizational commitment, and job stress as variables influencing employees' intention to leave the organization at Warung Cak Muk Restaurant in Mojokerto. This study is a quantitative research that draws conclusions based on statistically testing hypotheses. The research method employed is a survey method using a questionnaire as a tool to collect data from respondents. A sample of 60 respondents was taken using non-probability sampling techniques. The research instrument was tested for validity and reliability. Data analysis and hypothesis testing in this study involved multiple regression analysis using SPSS 25.0 data processing software. The results of the tests indicate a negative and significant impact of job satisfaction and organizational commitment on employees' intention to leave the organization. Meanwhile, job stress positively and significantly influences employees' intention to leave the organization. With these findings, it is expected that Warung Cak Muk Restaurant can develop strategies and plans to address the high level of employees' intention to leave the organization, thereby saving on significant operational costs.